2022
DOI: 10.1101/2022.04.22.489086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of the chromatin remodeler, ATRX, promotes aggressive features of osteosarcoma with increased NF-κB signaling and integrin receptor binding

Abstract: Osteosarcoma (OS) is a lethal disease with few known targeted therapies. Here we show that decreased ATRX expression is associated with more aggressive tumor cell phenotypes, including increased growth, migration, invasion, and metastasis. These phenotypic changes correspond with activation of NF-κB signaling, extracellular matrix remodeling, increased integrin αvβ3 expression, and ETS family transcription factor binding. Here we characterize these changes in vitro, in vivo, and in a dataset of human OS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 101 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…ATRX is one of the most frequently mutated genes in STS, along with TP53 and RB1 [ 4 ]. ATRX has wide-ranging cellular consequences, including a role in chromatin remodeling [ 30 ], telomere elongation [ 5 , 12 , 16 , 31 , 32 ], regulation of transcription, DNA repair, mitotic recombination [ 33 ], NF-kB signaling, and invasion [ 5 ]. Additional work has demonstrated that ATRX plays important roles in epigenetic regulation, modulating PRC2 activity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATRX is one of the most frequently mutated genes in STS, along with TP53 and RB1 [ 4 ]. ATRX has wide-ranging cellular consequences, including a role in chromatin remodeling [ 30 ], telomere elongation [ 5 , 12 , 16 , 31 , 32 ], regulation of transcription, DNA repair, mitotic recombination [ 33 ], NF-kB signaling, and invasion [ 5 ]. Additional work has demonstrated that ATRX plays important roles in epigenetic regulation, modulating PRC2 activity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement in molecular profiling and next-generation sequencing techniques, STS can be classified into unique subgroups [ 3 ], and such groupings may provide insight into prognostic or therapeutic insights for these patients. While the genomic underpinnings of STS are complex, three genes are consistently mutated in STS: TP53, RB1, and ATRX [ 4 , 5 ]. Although TP53 [ 6 8 ] and RB1 [ 9 ] are well-known tumor suppressors across many cancer types, ATRX is less well characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation